ASSESSMENT OF THE RESERVOIRSꞋ IMPACT ON THE RIVER FLOW (Journal of Geography and Environmental Management, 2022)
In this article, the influence of reservoirs and ponds on the hydrological regime in the Yesil River basin is studied. To assess the impact of existing reservoirs on the annual runoff of rivers in the study basin, a simplified methodology of the State Hydrological Institute was used. The change in the annual (seasonal) runoff under the influence of ponds and reservoirs was determined using two methods: by the volume of filling the reservoirs; due to additional evaporation from the water surface of reservoirs compared to evaporation from land before their creation. When assessing the impact of ponds in terms of filling volumes or taking into account in the direct form of water intakes for economic needs, the influence of not only ponds, as artificial elements of the landscape, but also other factors of economic activity, was revealed. When assessing the impact of economic activities on the elements of the hydrological regime of rivers, including the creation of reservoirs for long-term regulation, changes in the climatic background are taken into account. According to the analysis of the results of assessing the impact on the runoff of the volumes of filling reservoirs, economic activities from 1974 to 2018 led to a decrease in runoff in the alignment of the river. Yesil - Nur-Sultan in the middle years of water availability (50% supply) by 30%, and in the mouth section. Yesil - Petropavlovsk city decrease in runoff up to 7%.
Keywords: reservoir; evaporation; precipitation; anthropogenic impact on river runoff; reduction of river runoff; decrease in natural runoff